2013
DOI: 10.1186/1810-522x-52-48
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Bufo bankorensis distinguished by amplified restriction fragment length polymorphism of cytochrome b

Abstract: Background: Bufo bankorensis is an endemic species in Taiwan, and its populations are geographically and reproductively isolated. However, the distinction of Taiwanese B. bankorensis as a separate species from the Chinese Bufo gargarizans remains in dispute. Results: A primer set was designed to explore the mitochondrial (mt)DNA cytochrome (Cyt) b sequence (700 bp) of B. bankorensis in 148 individuals collected from 12 locations in Taiwan. After a polymerase chain reaction and sequencing, we found that the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The divergent genetic clades were found within B. bankorensis thus represent species polyphyly as a result of independent colonizations by previously diverged lineages of B. gargarizans complex. This is consistent with our recent study of genetic structure of B. bankorensis cyt b [96] , which concluded that one linage (western group 1, uncut by Bam HI and cut by Tsp RI) is most likely B. gargarizans , a second one (western group 2, uncut by both Bam HI and Tsp RI) is B. bankorensis , and a third one (eastern clade, cut by Bam HI but not cut by Tsp RI) may be a new subspecies. B. bankorensis has been historically recognized as one endemic species [28] , has distinct morphological characters as compared with B. gargarizans and is restricted to Taiwan, however the molecular evolutionary relationships fail to support this taxonomy.…”
Section: Discussionsupporting
confidence: 94%
“…The divergent genetic clades were found within B. bankorensis thus represent species polyphyly as a result of independent colonizations by previously diverged lineages of B. gargarizans complex. This is consistent with our recent study of genetic structure of B. bankorensis cyt b [96] , which concluded that one linage (western group 1, uncut by Bam HI and cut by Tsp RI) is most likely B. gargarizans , a second one (western group 2, uncut by both Bam HI and Tsp RI) is B. bankorensis , and a third one (eastern clade, cut by Bam HI but not cut by Tsp RI) may be a new subspecies. B. bankorensis has been historically recognized as one endemic species [28] , has distinct morphological characters as compared with B. gargarizans and is restricted to Taiwan, however the molecular evolutionary relationships fail to support this taxonomy.…”
Section: Discussionsupporting
confidence: 94%
“…This species has had a complicated taxonomic history (Hu et al 1984 ; Huang et al 1990 ; Macey et al 1998 ; Liang et al 2010 ), with several species being recognized as distinct or the same species as B. gargarizans (Fu et al 2005 ). Some molecular studies considered B. andrewsi , B. minshanicus , and B. tibetanus to be synonyms of B. gargarizans , while B. bankorensis is treated as a distinct species (Chen et al 2013 ; Yu et al 2014 ; Tong and Wo 2017 ; Frost 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies however, focusing on North East Asian mainland B. gargarizans populations, show a contrasting picture with some species showing genetic isolation, such as isolated peninsular or insular populations. This is demonstrated through the dichotomy between B. gargarizans and B. bankorensis , with the first species on the mainland and the latter in Taiwan ( Chen et al, 2013 ; Yu, Lin & Weng, 2014 ). Coastal North East Asia was potentially composed of several refugia during either glacial or interglacial periods, thus reducing gene flow connectivity, even for good dispersers such as raccoon dogs ( Kim et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bufo gargarizans populations have shown a slow decline in Korea throughout the last decades, mostly due to habitat partitioning ( Kuzmin et al, 2004 ). The genetic structure of populations in North East Asia is fairly well known for Chinese ( Liu et al, 2000 ; Fu et al, 2005 ; Zhan & Fu, 2011 ), Taiwanese ( Chen et al, 2013 ; Yu, Lin & Weng, 2014 ) and Japanese ( Hase, Shimada & Nikoh, 2012 ) populations, but very little is known so far for Korean populations ( Fu et al, 2005 ). Herewith, we hypothesise the absence of a total genetic segregation within B. gargarizans populations from South Korea due to the potential for recolonisation and population connectivity during interglacials.…”
Section: Introductionmentioning
confidence: 99%